Biocorona formation on gold nanoparticles modulates human proximal tubule kidney cell uptake, cytotoxicity and gene expression. (August 2017) - Ortega, M.T.; Riviere, J.E.; Choi, K.; Monteiro-Riviere, N.A.
Abstract: Gold nanoparticles (AuNP) adsorb macromolecules to form a protein corona (PC) after systemic delivery, to which the kidney as the primary excretory organ is constantly exposed. The role of the PC on AuNP cell uptake and toxicity was investigated in vitro in human proximal tubule cells (HPTC) using 40 and 80 nm branched polyethylenimine (BPEI), lipoic acid (LA) and polyethylene glycol (PEG) coated AuNP with or without (bare) PCs composed of human plasma (HP) or human serum albumin (HSA) for 0.25 to 24 h. Time-dependent intracellular uptake, assessed by ICP-MS showed PC modulated cell uptake and cytotoxicity; with bare 40 nm BPEI-AuNP showing the greatest responses. All AuNP showed minimal to no cytokine release. At the nontoxic dose, 40 nm bare BPEI-AuNP significantly modified gene expression related to immunotoxicity, steatosis, and mitochondrial metabolism; while at the high dose, pathways of DNA damage and repair, apoptosis, fatty acid metabolism and heat shock response were modulated. HP corona BPEI-AuNP response was comparable to control. These studies clearly showed reduced uptake and cytotoxicity, as well as differentiated gene expression of AuNP with PCs, questioning the utility of in vitro studies using bare NP to assess in vivo effects. Significantly, only cationic bare BPEI-AuNP had HPTC uptake or cytotoxicity suggesting the relative safety of PEG and LA-AuNP as nanomedicine constructs. Highlights: Cationic AuNP accumulate and exert toxicological effects in human kidney cells. Presence of a protein corona eliminates these outcomes. Gene expression profiles for BPEI particles were a function of applied dose. Anionic and neutral AuNP exert no detectable cell uptake or toxicological effects.